Using Audio Visual Learning Media to Improve Language Capability in Early Children in RA Dinda Hafidzah Islamic School Patumbak, Deli Serdang Regency, Academic Year 2021/2022 - Bella Ariska Mourentina; Novita Friska (International Journal of Educational Research Excellence (IJERE), 2022)
This research is a classroom action research. Classroom action research is one of the efforts that can be done by teachers to improve the quality of the roles and responsibilities of teachers in classroom management. Serdang Academic Year 2021/2022. data collection techniques using Observation, Documentation. Based on the results of the research conducted, this shows that the learning outcomes have not reached the success criteria, so it is necessary to carry out the second cycle of learning actions. In cycle II, the researcher made improvements to the delivery method of learning, but still with learning activities through the use of audio-visual media. After the second cycle of action, it is known that the development of children's language skills is developing, namely, a) Being able to listen and retell simple stories reaches 85.71%, b) Being able to imitate sounds or words according to the video seen reaches 100%, c) Able to answering simple questions reached 92.85%, d) Mentioning known words reached 85.71%.